2018
DOI: 10.1002/pat.4424
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of pH conditions and characterization of polyelectrolyte complexes between gellan gum and cationic guar gum

Abstract: The present study was aimed to investigate optimum pH conditions for polyelectrolyte complexation between gellan gum (GG) and cationic guar gum (CGG). The pKa of both the polymers was determined using potentiometric titrations. The complex formation was investigated at three pH values (based upon the pKa interval of two polymers) and at different mixing ratios (ranging from 10:90 to 90:10). Zeta potential and turbidity studies elucidated the optimum pH and mixing ratio at which maximum interaction takes place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 67 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…These changes in the -OH band position depicts the formation of Hbonding that strengthens with the incorporation of HPMC layer in composite lm. Further, the CGg spectra showed sharp bands at 1653 cm − 1 and 1445 cm − 1 depicting the presence of quaternary ammonium cations (Dai et al 2020;Kaur et al 2018). In case of CGg/cCNCs and CGg/cCNCs/HPMC multilayered composite lm the characteristic band appeared at around 1635 cm − 1 which can be related to the electrostatic interactions between carboxylate groups of cCNCS and quaternary ammonium cations of CGg and the overlapping of characteristic bands of CGg and cCNCs (Dai et al 2020;Kaur et al 2018).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…These changes in the -OH band position depicts the formation of Hbonding that strengthens with the incorporation of HPMC layer in composite lm. Further, the CGg spectra showed sharp bands at 1653 cm − 1 and 1445 cm − 1 depicting the presence of quaternary ammonium cations (Dai et al 2020;Kaur et al 2018). In case of CGg/cCNCs and CGg/cCNCs/HPMC multilayered composite lm the characteristic band appeared at around 1635 cm − 1 which can be related to the electrostatic interactions between carboxylate groups of cCNCS and quaternary ammonium cations of CGg and the overlapping of characteristic bands of CGg and cCNCs (Dai et al 2020;Kaur et al 2018).…”
Section: Resultsmentioning
confidence: 93%
“…Further, the CGg spectra showed sharp bands at 1653 cm − 1 and 1445 cm − 1 depicting the presence of quaternary ammonium cations (Dai et al 2020;Kaur et al 2018). In case of CGg/cCNCs and CGg/cCNCs/HPMC multilayered composite lm the characteristic band appeared at around 1635 cm − 1 which can be related to the electrostatic interactions between carboxylate groups of cCNCS and quaternary ammonium cations of CGg and the overlapping of characteristic bands of CGg and cCNCs (Dai et al 2020;Kaur et al 2018). Further the band at 1445 cm − 1 shifted to lower wavenumber at 1425 cm − 1 for CGg/cCNCs lm, suggesting the strong electrostatic interaction or H-bonding between CGg and cCNCs (Dai et al 2017;Kaur et al 2018).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, it was suggested that flexibility and hardness can be better controlled through blends with natural and synthetic polymers [ 103 ]. The negative charge of gellan allows the production of polyelectrolytes with other oppositely charged polymers such as chitosan and cationic guar gum [ 104 , 105 ]. The gelling properties of gellan gum depend on several factors such as the presence of cations, pH, temperature, and polymer concentration [ 103 , 106 ].…”
Section: Composition Of Edible Coatingsmentioning
confidence: 99%
“…Mass ratio G:C = 5:10, 6:12, 7:14 [58] Tragacanth gum (T) Insulin (I) (% w/w) ratio T:I = (0.1, 0.5, 1): 0.02, pH of Tragacanth was adjusted to 3.7, 4.3, 4.6 or 6 [59] Xanthan gum Chitosan % weight ratio X:C = 1.5:1.5 [60] Gellan gum Cationic guar gum Mixing ratios G:CGG = 10:90 until 90:10, pH 3.72, 5.5, and 7.13 [61] Okra gum (O) Chitosan Ratio O:C = 10:90 until 90:10, pH 5.0 [62] Xanthan gum Chitosan (% w/v) ratio X:C = 0.5:0.5 [63] Gellan gum Chitosan Ratio G:C = 10:90 until 65:35, 60 Arabinogalactans gum acacia (GA)…”
Section: Gellan Gum Chitosanmentioning
confidence: 99%